IMPACT OF EFFECTIVE CORPORATE TAX INCENTIVES ON FDI (International Journal of Psychosocial Rehabilitation, 2020)
The essential objective for conducting this research is to measure the significant effectiveness of corporate tax rates and inflow of direct investment. This paper includes the empirical analysis that studies the case of developed and developing countries in the last three decades. The model is developed based on the previous researches. On the other hand, some previous studies mentioned there was no relationship between effective corporate tax and FDI in particularly in some developed i.e. Germany, Turkey, etc. while other studies have founded a significant relationship between those two. In addition, there are several other common factors effected in FDI.